PELATIHAN PENGOPERASIAN ALAT PENGHANCUR DAN PENGADUK KOTORAN HEWAN (KOHE) TERINTEGRASI DI CV TIGA LIMA JAYA DESA JAJAR GUMREGAH - lestari, Wahyu Dwi; Edahwati, Luluk; Harya, Gyska Indah (Jurnal Abdi Insani, 2024)
Training on the use of an integrated animal manure crusher and mixer (KOHE) at CV Tiga Lima Jaya aims to improve the efficiency of animal manure management as an ingredient for making organic fertilizer and employee skills. This training includes basic theory of machine operation, practical demonstrations, maintenance, and troubleshooting. The method of implementing this community service activity includes preparation, implementation, and evaluation or follow-up. The results of the training showed an improvement in employee knowledge and skills, with an increase in theory evaluation scores from 55% to 90% and 88% and employees were able to operate the machine independently. Operational efficiency improved, KOHE processing time from 5 hours to 2 hours per day, and processing capacity increased by 50%. The training also contributed to the SDGs, specifically in clean and affordable energy (SDG 7), decent work and economic growth (SDG 8), and industry, innovation and infrastructure (SDG 9). Future recommendations include continuous training, environmental impact measurement, cooperation with educational institutions, implementation of new technologies, and infrastructure improvements.